„Wirtualny doradca zdrowotny”, suplement diety, reklama i odbiorca – czyli język portali promujących zdrowie w Internecie - Błachowicz, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The paper focuses on the language of the health promoting web portals, including the language of advertisements related to the health promoting products which are placed on selected web portals. The communication-related aspect of the discussion, that is the perspective of the virtual health advisor and receiver organise the discussion. The analysis is conducted according to the paradigm of the popular science apparatus with limited amount of specialist terminology, which makes it understandable for any reader.
Keywords: health-related web portals; language promoting health on the Internet; advertisement